2019
DOI: 10.1080/1343943x.2018.1561195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different water management practices on the dry matter production process and characteristics in NERICAs

Abstract: In this study, we aimed to clarify the effects of different water management strategies on dry matter production and yield performance of New Rice for Africa (NERICA) varieties. Dry matter production of NERICA 1 and NERICA 5 was compared with that of Yumenohatamochi, a Japanese upland variety, and Hinohikari, a Japanese lowland variety under three water regimes, i.e. continuously flooded, supplemental irrigation, and non-irrigation (rainfed). Total carbohydrate content in the panicles under different watering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…These results are consistent with the findings reported by Kikuta et al. (2019) that reduced crop growth resulting from decreased NAR from the panicle initiation to maturity stage suppressed dry matter production and grain yield under intermittent irrigation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are consistent with the findings reported by Kikuta et al. (2019) that reduced crop growth resulting from decreased NAR from the panicle initiation to maturity stage suppressed dry matter production and grain yield under intermittent irrigation.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, water stress decreases the leaf photosynthetic rate, thereby reducing NAR (Lu et al. 2000; Praba et al., 2009) and RGR shows a much stronger correlation with NAR than with LAR under water deficit conditions (Kikuta et al., 2019). These findings suggest that the our1 ‐type genotypes maintained a high growth rate from the heading to maturity stages under AWD through increased photosynthetic ability (Table ), resulting in higher dry matter production and grain yield.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, lateral root formation may be induced by carbohydrate allocation, which is supported by the exogenous glucose application that promotes L-type lateral roots (Lucob-Agustin et al 2020c). Recently, Kikuta et al (2019) observed that some drought-tolerant rice varieties could use basal shoot starch for root development during the heading period for the maintenance of yield production under water-limited conditions. These studies highlighted a novel physiological action of both the shoot and root in the regulation of root plasticity in rice.…”
Section: Regulation Of Phenotypic Root Plasticity Via Carbohydrate Allocationmentioning
confidence: 99%